The Health Literacy of First Year Students at State Polytechnic of Creative Media - Antinah Latif; Meisi Riana (Politeknik Negeri Media Kreatif, 2020)
Health literacy is one of the important sosial determinants to improve health and well-being. The results of health literacy can be beneficial for health professionals to understand the concept of intervention. The study objective was to determine the level of health literacy, sosial determinants and access to health information for first year students. 49 men and 76 women first year students volunteered to participate in completing HLS-SF-Q12. The analysis used was univariate and bivariate (Mann-Whitney test). The results showed no significant relationship between sosial determinant variabels with health literacy, the highest domain of literacy level in health promotion, and health information was one of the topics most rarely accessed. It is suggested that the use of campus media to improve the health literacy domain of vocational student health care. Access to information can be acessed through various media appropriate to students' socio-culture.